Occurrence of fungi on Sparaxis sp. corms cultivated near Lublin - Agnieszka Piwoni (Acta Agrobotanica, 2012)
The healthiness analysis of Sparaxis sp. corms was carried out in the years 2002-2003 on the experimental fields of The Agricultural University near Lublin. Plants were cultivated in trials treated with: Asahi SL (sodium nitrophenole derivates), Tytanit (tytanium), herbicides: Afalon 450 SC (linuron), Devrinol 450 SC (napropamide), Stomp 400 SC (pendimethaline) and in control trial without treatment. The healthiness was evaluated after digging and after storage. Among fungi isolated from sparaxis corms after digging and storage, the species Fusarium oxysporum predominated. The corms infected with it were deformed, wrinkled and covered with brown, scaby lesions. This species also dominated among fungi isolated from all the trials, regardless a preparation applied. The disease index values ranged within 6.0 - 9.25 after digging and within 9.25 - 15.75 after storage respectively. There was no a marked positive effect of a used preparation on the healthiness of sparaxis corms.